Implementasi Sistem Zonasi dalam Mewujudkan Keadilan Sosial di Sekolah - Asih Agus Nur Cahya.N; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The zoning system for new student admissions is an educational policy aimed at achieving equitable access and social justice in education. This policy was implemented to reduce the gap between favored and non-favored schools and provide equal opportunities for all students to access educational services. However, various problems remain in its implementation, such as disparities in school quality, limited educational facilities, and the emergence of pros and cons in the community. Therefore, this research is crucial to understand the implementation of the zoning system in realizing social justice in schools.This study aims to analyze the implementation of the zoning system in realizing social justice in at SMKN Ngambon and identify obstacles encountered in its implementation. This study used qualitative research methods with a descriptive approach. Data were obtained through observation, interviews, and documentation. Observations were conducted to observe the implementation of the zoning system in schools, interviews with principals, teachers, and students, and documentation was used to obtain supporting data related to the zoning policy. Data sources consisted of primary and secondary data. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The research results show that the implementation of the zoning system has had a positive impact on equalizing access to education and increasing student diversity in schools. The zoning system also promotes social justice through more equitable learning opportunities for the community. However, the implementation of this policy still faces several obstacles, such as differences in school quality, limited infrastructure, and poor public understanding of the objectives of educational zoning.The study concludes that the zoning system plays a crucial role in realizing social justice in education, but its implementation requires more optimal support from the government, schools, and the community. Equitable distribution of educational quality, improved school facilities, and ongoing policy dissemination are necessary to maximize the goals of the zoning system.